Assessment of the quality and content of website health information about herbal remedies for menopausal symptoms. (June 2016) - Sowter, Julie; Astin, Felicity; Dye, Louise; Marshall, Paul; Knapp, Peter
Highlights: Commercial website providers had lower-quality information about herbal remedies for menopausal symptoms than non-commercial providers. Information coverage was poor for both provider types and the required reading level was high. There was a positive correlation between website quality and information coverage. Abstract: Objective: To assess the quality, readability and coverage of website information about herbal remedies for menopausal symptoms. Study design: A purposive sample of commercial and non-commercial websites was assessed for quality (DISCERN), readability (SMOG) and information coverage. Main outcome measures: Non-parametric and parametric tests were used to explain the variability of these factors across types of websites and to assess associations between website quality and information coverage. Results: 39 sites were assessed. Median quality and information coverage scores were 44/80 and 11/30 respectively. The median readability score was 18.7, similar to UK broadsheets. Commercial websites scored significantly lower on quality (p = 0.014), but there were no statistical differences for information coverage or readability. There was a significant positive correlation between information quality and coverage scores irrespective of website provider (r = 0.69, p < 0.001, n = 39). Conclusion: Overall website quality and information coverage are poor and the required reading level high.